Walking in Both Worlds: Learning about Youth Priorities and Indigenous Food Sovereignty with Délįnę’s Youth Council - MacLeod Farley, Neala (Scholars Commons @ Laurier, 2022)
Indigenous food sovereignty is vital to the protection and restoration of Indigenous food systems and to many Indigenous peoples’ health, culture, and traditions. Working towards Indigenous food sovereignty can also help to enable the protection and continued development of Indigenous knowledge and worldviews, which are becoming increasingly recognized for their potential to help transform unsustainable food systems and combat climate change. In Délįnę, Northwest Territories (NWT), re-establishing intergenerational knowledge transfer to today’s youth is an essential aspect of food sovereignty and the continuation of Dene worldviews. However, this is challenging for many youth as they face conflicting pressures from Western and Indigenous cultures and ways of life. This thesis, grounded in community-based participatory action research and an Indigenist research paradigm, explores the perspectives of youth in Délįnę, including those involved with the newly formed Tsá Tué Youth Council. Through a thematic analysis of youth recommendations made at a community visioning session and in-depth interviews, the priorities of youth, barriers they face in engaging and affecting change, strengths they have to build off of, and potential solutions are explored in relation to Indigenous food sovereignty.